Phytochemical Analysis And Standardization of Pathyadi Ghana Vati - An Ayurvedic Polyherbal Formulation For Migraine - Mansi; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2021)
Background: Migraine is a common neurovascular ailment with a significant impact on quality of life. It simulates with the Shiroroga (diseases of head) called Ardhavbhedaka in Ayurveda. Pathyadi Kwatha is a very famous and commonly prescribed classical formulation in Ardhavbhedaka and various other types of headache. Despite the fact that the formulation is mentioned in the classical texts in the form of Kwatha (decoction), it was converted to the tablet (Ghana Vati) form as it is palatable, easy to dispense, and has prolonged shelf life. Objective and methods: The present study was designed to standardize the finished product, Pathyadi Ghana Vati, by evaluation of its organoleptic, Physico-chemical, phytochemical and chromatographic parameters. Results: Physico-chemical analysis revealed pH value 7.0, Alcohol soluble extract 29.10%, water soluble extract 82.05 %, Ash value 2.15%, and phytochemical analysis showed the presence of alkaloids, amino acids, saponins, phenolic compound, and tannins. Conclusion: The parameters presented in this paper may serve as a standard reference for the quality control analysis of Pathyadi Ghana Vati.